KONTRIBUSI USAHA PEMBUATAN BERAS SINGKONG BAGI PENDAPATAN KELUARGA PADA KELOMPOK TANI SUMBER JAYA DI DESA TEMPILANG KECAMATAN TEMPILANG KABUPATEN BANGKA BARAT - Rominah, Rostiar Sitorus, Evahelda dan (Jurnal Buana Agribisnis, 2014)
ABSTRACTThis study aims to determine the profile of the business of making cassava rice, cassava and rice marketing channels raise the profile of the business, the income received and the contribution to the family income of Sumber Jaya Farmers. Primary and secondary data were obtained and analyzed by study case method. The results show that the Sumber Jaya Farmers engaged in the processing of food crops to process cassava into cassava rice. Making rice cassava includes several stages, supplies of raw materials, stripping, washing, soaking, making flour, the first pressing, pulverization, pressing the second, the formation of granules, drying, packaging. Net revenues from the manufacture of cassava rice per month is Rp 1,064,283. Rice and cassava production business contribution to total revenue Family Farmers Jaya source is 5.0%.Keywords: Cassava Rice, contributions, income farm families